From Symbolic Green Claims to Operational Impact: A Decision-Oriented AHP 7P Framework for Sustainable Coffee Shops - Saliha, Ilmiasa; Ismoyowati, Dyah; Ainuri, Makhmudun (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractThe growth of urban coffee shops strengthens the economic contribution of the hospitality sector while increasing environmental pressure through intensive consumption of energy, water, and materials. Green marketing studies in this sector still focus on consumer perception and symbolic communication, lacking a measurable, operational, and strategically prioritized framework. This study offers a structured decision-making approach by integrating the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) and the Analytical Hierarchy Process (AHP) based on environmental expert assessments. The study aimed to identify green marketing strategies that are relevant, impactful, and realistic for small-scale coffee shops. A multi-criteria approach consolidated 23 attributes into 8 operational strategies, then ranked them through pairwise comparisons by six environmental experts following interviews with 21 business owners. All consistency ratios were below 0.10. Results showed that the People, Process, and Physical Evidence dimensions had the highest weighting. Internalization of employee green behavior ranked first, followed by operational resource efficiency and the use of energy- and water-efficient equipment, while price incentives and environmental donations ranked lower. The findings confirm that internal process control and behavioral discipline are the foundations of sustainability and support replication and scale-up of green practices to strengthen competitiveness and reduce environmental impact.Keywords: Analytical Hierarchy Process, green marketing, resource efficiency, strategy prioritization, sustainable coffee shop AbstrakPertumbuhan coffee shop perkotaan memperkuat kontribusi ekonomi sektor hospitality sekaligus meningkatkan tekanan lingkungan melalui konsumsi energi, air, dan material yang intensif. Kajian pemasaran hijau pada sektor ini masih berfokus pada persepsi konsumen dan komunikasi simbolik sehingga belum menyediakan kerangka prioritas strategis yang terukur dan operasional. Penelitian ini menawarkan pendekatan pengambilan keputusan terstruktur melalui integrasi bauran pemasaran 7P (Product, Price, Place, Promotion, People, Process, dan Physical Evidence) dan Analytical Hierarchy Process (AHP) berbasis penilaian ahli lingkungan. Tujuan penelitian adalah menyusun urutan prioritas strategi pemasaran hijau yang relevan, berdampak, dan realistis diterapkan pada coffee shop skala kecil. Metode menggunakan pendekatan multi kriteria dengan konsolidasi 23 atribut menjadi 8 strategi operasional lalu diperingkatkan melalui perbandingan berpasangan oleh 6 ahli lingkungan setelah wawancara terhadap 21 pemilik usaha. Seluruh rasio konsistensi berada di bawah 0,10. Hasil menunjukkan dimensi People, Process, dan Physical Evidence memiliki bobot tertinggi. Internalisasi perilaku hijau karyawan menempati peringkat pertama, diikuti efisiensi sumber daya operasional dan penggunaan peralatan hemat energi dan air, sedangkan insentif harga dan donasi lingkungan berada pada posisi lebih rendah. Temuan menegaskan bahwa pengendalian proses internal dan disiplin perilaku menjadi fondasi keberlanjutan. Kerangka ini mendukung replikasi dan scale-up praktik hijau guna memperkuat daya saing dan menurunkan dampak lingkungan sektor hospitality.Kata kunci: Analytical Hierarchy Process, coffee shop berkelanjutan, efisiensi sumber daya, green marketing, prioritisasi strategi